Pathogenicity to Mekong Giant Catﬁ sh Eggs of Water Moulds Isolated in the Laboratory from Mekong Giant Catﬁsh Eggs and Rearing Water - Abking, Narong; Fuangsawat, Wichukarn; Lawhavinit, Ong-ard (Agriculture and Natural Resources, 2012)
Water moulds in the genera Achlya and Saprolegnia were isolated from eggs of the Mekong giant catﬁsh (Pangasianodon gigas) and from the water in the hatching tank at the Inland Aquaculture Research Institute, Phra Nakhon Sriayutthaya province, from 2008 to 2010. The optimal temperature of almost all isolates was 30 °C. The Achlya spp. and Saprolegnia spp. could tolerate an NaCl medium at 10 and 25 parts per trillion (ppt), respectively. An exception was Saprolegnia sp. (E3/52-P2) which could tolerate NaCl up to 30 ppt. The isolates could grow in broth at pH 4–11, while the optimal pH for Achlya spp. and Saprolegnia spp. was pH 5 and pH6, respectively. The study on pathogenicity of the water moulds isolated in the laboratory showed that the isolates Achlya spp. (T.MCF1-02, E.MCF 2-001 and E4/52-10) and Saprolegnia sp. (E1/53-12) were pathogenic to the catﬁsh eggs.